Analysis of Financial Ratios of Thai National Football Shirt Production Companies - Waraporn Suksanchananun; Suradetch Wangthong; Gunyanuch Kittipongpittaya (International Journal of Business and Applied Economics, 2023)
The purpose of this study was to analyze the financial status of the performance sports clothing industry. The sample group used a specific random method for the company that produces Thai national football team shirts. The tools used in the study were an analysis of financial ratios using secondary data from the annual financial statements of Thai national football shirt manufacturing companies from 2021 to 2022. The study found that the overall performance of the company was satisfactory, with the proportion of non-current assets significantly decreasing, equity increasing to a level that exceeds liabilities, and the ability to control selling and administrative expenses improving by leaps and bounds. The company's net profit has increased, the liquidity ratio has increased, the efficiency ratio for accounts receivable has decreased, the efficiency of inventory has improved, total assets and fixed assets have improved, and the debt service coverage ratio has also improved.